Protection of Workers' Legal Rights Against Unilateral Termination of Employment (Analysis of Decisions 83/Pdt.Sus-PHI/2020/PN.Mdn and 105/Pdt.Sus-PHI/2021/PN.Mdn) - Hasim Purba; Agusmidah; Stefani Kamajaya (Journal Equity of Law and Governance, 2024)
Employees and workers may be fired by a firm as long as it complies with the procedures and requirements outlined in the Manpower Law. But it is not acceptable to fire a worker or employee arbitrarily or for not following the correct procedure. This work is normative juridical legal research with analytical descriptive research features. Legal papers gathered through literature review procedures, classified as primary, secondary, and tertiary, make up the secondary data that is employed. Techniques from qualitative analysis were used in the data analysis process. Although the Manpower Law enables unilateral the termination of employment (PHK) due to efficiency and business closure, based on reduced productivity, is allowed under Law No. 6/2023, often known as The Regulations on the creation of work. This law permits layoffs without necessitating the company's closure. As per the terms of legislation 6/2023, the Creation of Industries Act, layoffs are outside the jurisdiction of the Industrial Relations Court (PHI). The Termination of Finding work, however (PHK) process under the Manpower Law requires direct negotiation between the employer and employee. The panel of judges examined the legislation in Decision Numbers 83/Pdt.Sus-PHI/2020/PNMdn and 105/Pdt.Sus-PHI/2021/PNMdn with the aim of safeguarding the rights of employees who were terminated unjustifiably. This entailed bestowing upon the plaintiff the rights specified by the Labor Law. Although the judge did not take into account the Job Creation Law (Law No. 2/2020) that was in existence at the time, it is believed that the verdict adequately safeguards the rights and provides legal protection of employees who were fired without cause.